Development of Learning Materials Based on the MURDER Collaborative Learning Model to Enhance Students’ Conceptual Understanding of Mathematics - Rahmayani, Sri; Afnaria, Afnaria; Azis, Zainal (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The low level of students’ conceptual understanding in mathematics highlights the need for innovative and structured learning approaches. This study aims to develop mathematics learning materials based on the MURDER collaborative learning model (Mood, Understand, Recall, Digest, Expand, and Review) to enhance students’ conceptual understanding. The research employed a Research and Development (R&D) design involving expert validation, limited trials, and classroom implementation to evaluate the validity, practicality, and effectiveness of the developed module. The model helps students recall and comprehend mathematical concepts more effectively, supporting both teaching and learning processes in the classroom. The product was validated by three expert groups. Content validation produced an average score of 88.2%, media validation 92.5%, and language validation 85.5%, with an overall mean of 88.7%, indicating that the module is highly feasible. Practicality testing, based on student response questionnaires, yielded an average score of 82%, classified as highly practical. Effectiveness testing in a Grade 10 science class involving 30 students resulted in a mean score of 83.6%, categorized as highly effective. Furthermore, the N-Gain value of 0.81demonstrates a high improvement in students’ conceptual understanding after using the module. These results confirm that the MURDER-based mathematics learning module is valid, practical, and effective for improving students’ conceptual understanding, particularly in learning the sine and cosine rules. The developed module can serve as a reference for schools and educators seeking to implement collaborative and conceptually oriented mathematics learning.